Exploring Different Types of Inhibition During Bilingual Language Production - Borragan, Maria; Martin, Clara D.; de Bruin, Angela; Duñabeitia, Jon Andoni (Frontiers in Psychology, 2018)
Multilinguals have to control their languages constantly to produce accurate verbal output. They have to inhibit possible lexical competitors not only from the target language, but also from non-target languages. Bilinguals’ training in inhibiting incongruent or irrelevant information has been used to endorse the so-called bilingual advantage in executive functions, asumming a transfer effect from language inhibition to domain-general inhibitory skills. Recent studies have suggested that language control may rely on language-specific inhibitory control mechanisms. In the present study, unbalanced highly proficient bilinguals completed a rapid naming multi-inhibitory task in two languages. The task assessed three types of inhibitory processes: inhibition of the non-target language, inhibition of lexical competitors, and inhibition of erroneous auditory feedback. The results showed an interaction between lexical competition and erroneous auditory feedback, but no interactions with the inhibition of the non-target language. The results suggested that different subcomponents of language inhibition are involved during bilingual language production.